PERAN NYAI HAMDANAH DALAM SEJARAH ISLAM DI NUSANTARA - Abdul Muttholib; Nicky Estu Putu Muchtar (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
The role of Muslim women is actually not just to demand equal rights, but to express the function of women who have meaning for development in the trajectory of Islamic history in the archipelago. The potential of women as human resources can be seen in efforts to include women's roles in the development process starting from upstream to downstream that are sustainable, humane, moderate, tolerant, straight as well as actions that prioritize efficiency. Excluding the role of women in the development process means a waste of resources and negatively affects the pace of growth and development on all fronts; religious, educational, social, and also economic. The role of women involves the role of tradition and transition, or we know it as domestic and public. Nyai Hamdanah is one of the female figures who has an important role in the history of Islam in the archipelago.  The role of Nyai Hamdanah in accompanying two pious and allamah husbands in service and da'wah can be used as a reference to give birth and produce strong and characterful sons and daughters of the nation's generation.